ChemInform Abstract: Transition Metal Complexes in Supported Liquid Phase and Supercritical Fluids — A Beneficial Combination for Selective Continuous‐flow Catalysis with Integrated Product Separation. Issue 8 (1st March 2013) - Hintermair, Ulrich; Chinnusamy, Tamilselvi; Leitner, Walter
Abstract Review: 158 refs.